A Study of the Feasibility of Network Tutorial System in Taiwan - Chiu, Jui-Man; Liu, Wei-Liang (Educational technology & society, 2008)
The reasons that the current tutorial system (CTS) does not produce significant effects include the budgets and policies of schools, the greater independence of students, and the infrequent interaction of tutors with students. To reduce the deficiencies of the current tutorial system, this paper proposes a network tutorial system (NTS) and discusses the feasibility of the NTS. We use factor analysis to find the emphasized key factors of tutors, the counselors of student counseling centers (abbreviated as counselors), and students, respectively, about the feasibility of the NTS. Also, we use t test to check whether the mean opinion of male students and that of female students have significant difference with respect to each evaluation item of the feasibility of the NTS. Taiwanese universities and colleges are used as the research subjects. The empirical results show that the most emphasized factor of the tutors and students is “privacy esteem.” The most emphasized factor of the counselors is “the efficiency enhancement of counseling due to the NTS.” The gender differences of students do not influence the evaluation results of them for the feasibility of the NTS.